A new one time password mechanism for client-server applications. (17th November 2019) - Shukla, Varun; Chaturvedi, Atul; Srivastava, Neelam
Abstract: OTP (One Time Passwords) are very important in today's scenario in various applications like in financial transactions, e-commerce etc. They are used for enhancing the security of data communication. Many security applications are based on the strength of OTP. Any prediction in OTP generation can create serious threats to information security. Many new methods have been presented by researchers for OTP generation in the past decade. In this paper, we present a new authenticated OTP generation procedure between client and server. We also provide illustration with complete security analysis in order to prove its utility in various applications. Our procedure is implementable very easily and has embedded authentication and randomness.